A multifunctional composite membrane with photocatalytic, self-cleaning, oil/water separation and antibacterial properties. (27th August 2022) - Zhang, Yubo; Chen, Yi; Wang, Chen; Fan, Zhao; Wang, Yongqian
Abstract: Multifunctional composite materials have attracted wide attention because they can be applied in many fields, and have great potential for application. The superhydrophobic surface has been favored by scientists in recent years because of its excellent properties. In this paper, carbon fabric (CF) with high porosity, good electrical conductivity and excellent flexibility was selected as substrate. The CF/Zr–TiO2 /PDMS composites were prepared by solvo-thermal method on CF and modified by PDMS, which can be used in the fields of self-cleaning, self-healing, oil/water separation, antibacterial, anti-icing and so on. Furthermore, the PDMS modification has no or negligible adverse effect on the important textile physical properties of the CF. The effects of different process parameters on the structure and properties of CF/Zr–TiO2 were studied, and the samples with the best conditions were obtained. The results show that the sample achieves the transformation from superhydrophilic to superhydrophobic after modification. The CF/Zr–TiO2 /PDMS composite structure not only shows excellent photocatalytic activity, but also has a certain self-cleaning ability. The samples before and after modification can separate light oil/water and heavy oil/water respectively. Compared with CF/Zr–TiO2, CF/Zr–TiO2 /PDMS has better anti- Escherichia coli ability.